ANALISIS YURIDIS PENGGUNAAN ASET PERSONAL GUARANTEE DALAM MELUNASI UTANG PAILIT - Putri Avi Avivah; Eddie Imanuel Doloksaribu (Fakultas Hukum Universitas Katolik Indonesia Atma Jaya, 2021)
In bankruptcy, the use of personal guarantee assets is something that can be done in bankruptcy debt if the assets belonging to the main debtor cannot meet repayments, in bankruptcy, there are 3 types of credit, namely preferred, separatist and concurrent creditors, the three creditors are creditors who have rights and obligations. their respective positions, such as preferred creditors who have the priority right to have their debts repaid, then separatist creditors who have collateral to pay their debts, and separatist creditors who do not have collateral rights or the right to loans. If the debtor's payment to the creditor exceeds the limit after the assets of the main debtor have been auctioned, therefore the responsibility of the Personal Guarantee is to provide the assets in paying off the debt of the main debtor. Personal guarantee assets are guarantees that can be used to pay off their debts because if the assets belonging to the main debtor cannot be sufficient to pay the total debt, the personal guarantee will be responsible for settlement, the assets belonging to the personal guarantee can be directly auctioned, the payment of the bankruptcy debt is calculated by method “Pro Rata Pari Passu Parte”. The Personal Guarantee which guarantees its assets to creditors can also be bankrupt if the main debtor is unable to pay its debts.